C‐terminal agrin fragment as a biomarker of muscle wasting and weakness: a narrative review. Issue 2 (11th February 2023) - Monti, Elena; Sarto, Fabio; Sartori, Roberta; Zanchettin, Gianpietro; Löfler, Stefan; Kern, Helmut; Narici, Marco Vincenzo; Zampieri, Sandra
Abstract: Ageing is accompanied by an inexorable loss of muscle mass and functionality and represents a major risk factor for numerous diseases such as cancer, diabetes and cardiovascular and pulmonary diseases. This progressive loss of muscle mass and function may also result in the insurgence of a clinical syndrome termed sarcopenia, exacerbated by inactivity and disease. Sarcopenia and muscle weakness yield the risk of falls and injuries, heavily impacting on health and social costs. Thus, screening, monitoring and prevention of conditions inducing muscle wasting and weakness are essential to improve life quality in the ageing modern society. To this aim, the reliability of easily accessible and non‐invasive blood‐derived biomarkers is being evaluated. C‐terminal agrin fragment (CAF) has been widely investigated as a neuromuscular junction (NMJ)‐related biomarker of muscle dysfunction. This narrative review summarizes and critically discusses, for the first time, the studies measuring CAF concentration in young and older, healthy and diseased individuals, cross‐sectionally and in response to inactivity and physical exercise, providing possible explanations behind the discrepancies observed in the literature. To identify the studies investigating CAF in the above‐mentioned conditions, all the publications found in PubMed, written in English and measuring this biomarker in blood from 2013 (when CAF was firstly measured in human serum) to 2022 were included in this review. CAF increases with age and in sarcopenic individuals when compared with age‐matched, non‐sarcopenic peers. In addition, CAF was found to be higher than controls in other muscle wasting conditions, such as diabetes, COPD, chronic heart failure and stroke, and in pancreatic and colorectal cancer cachectic patients. As agrin is also expressed in kidney glomeruli, chronic kidney disease and transplantation were shown to have a profound impact on CAF independently from muscle wasting. CAF concentration raises following inactivity and seems to be lowered or maintained by exercise training. Finally, CAF was reported to be cross‐sectionally correlated to appendicular lean mass, handgrip and gait speed; whether longitudinal changes in CAF are associated with those in muscle mass or performance following physical exercise is still controversial. CAF seems a reliable marker to assess muscle wasting in ageing and disease, also correlating with measurements of appendicular lean mass and muscle function. Future research should aim at enlarging sample size and accurately reporting the medical history of each patient, to normalize for any condition, including chronic kidney disease, that may influence the circulating concentration of this biomarker.